A novel quantitative trait locus on chromosome 7D derived from Aegilops tauschii confers moderate field resistance to wheat blast - Xinyao He; Cong Li; Kishii, Masahiro; Soichiro Asuke; Kabir, Muhammad R.; Roy, Krishna K.; Butron, Roberto; Chawade, Aakash; Yukio Tosa; Pawan Kumar Singh (American Phytopathological Society, 2025)
Wheat blast is a devastating disease in the tropical and subtropical regions of South America and has recently spread to Bangladesh and Zambia. Host resistance to this disease has primarily relied on the 2NS/2AS translocation, making it crucial to identify and utilize novel sources of resistance. In the current study, a recombinant inbred line population consisting of 345 BC1F4 progenies was generated, using the susceptible wheat genotype 'Gladius' as the female and recurrent parent and the resistant Aegilops tauschii line 'KU-2097' as the male parent. Field phenotyping was conducted at two locations in Bolivia and one in Bangladesh, each with two sowing dates, during the 2022/2023 or 2023 cropping cycles. Genotyping was performed using DArTseq technology. Quantitative trait locus (QTL) mapping identified a major and consistent QTL on the long arm of chromosome 7D, designated as Qwb.cim-7D, which explained 7.7 to 50.6% of the phenotypic variation across different experiments. The DArTseq markers in the QTL region were converted to KASP markers, enabling the precise mapping of this QTL to a genomic region between 619.90 and 625.61 Mb, flanked by the KASP markers K3222157 and K1061589. This novel QTL, along with its flanking markers, could be valuable for breeding programs targeting wheat blast resistance.